France: From Incremental Transitions to Institutional Change (Springer Netherlands)
French public institutions are often assumed to be reform adverse. This assumption is confirmed by many events in the history of French higher education (HE) and research systems. Quite recently (2003), the government withdrew a project, aimed at increasing the strategic and operational resources of public universities, from submission to the Parliament to avoid students' and academics' unrest. A social movement also developed in 2004 among researchers protesting against awkward manoeuvres by the government to induce more flexibility in the public sector research labour force. Reforms are usually opposed because they might favour differentiation between universities and jeopardize the national dogma of equality of treatment. The 1986 Devaquet act collapsed because it allowed universities to set, within a very restricted frame, their fees. The same happened in 1993 when the Fillon act offered new status choices to universities. They could have replaced the uniform status created by Savary in 1984 by a more managerial one, first created to help developing newly created universities in the 1990s. The unions opposed the proposal as they saw it as a threat against the principle of equality (see Merrien and Monsigny, 1996 or Merrien and Musselin, 1999)

(untitled) - Musselin, Christine; Paradeise, Catherine (University Governance, 2009)